News translation in the digital age: A case study of Vice.com - Putri, Annisa Cinantya (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2019)
Translation-mediated events get circulated globally through the media. This paper focuses on studying how events in, about, and pertaining Indonesia in general are presented to the foreign audience through translation. To that end, this paper employs descriptive product-oriented approach and translation transformation strategies adapted from those proposed by translation scholars. The data were collected from an online media, VICE Indonesia, and were limited to Indonesian source texts and their English target texts published in November 2018. Following initial data collection, 10 pairs of target and source texts were compiled for comparative analysis. Data analysis revealed that adaptation and re-contextualization of target texts occurred. They are found most prominently in the title and lead sections, although an analysis on the articles’ content also show that the target texts’ contents also experience similar changes. Among these changes, the most noticeable are recomposition of paragraphs, omission and substitution or paragraphs, and different choice of source of quote. Ultimately, although the target texts maintain to some degree of semblance to the source texts, new realities and perspectives emerge as the result of these translation strategies.